Gambaran Kualitas Kehidupan Kerja Perawat Di Ruang Rawat Inap RSUD Ajibarang - Purnomo, Safik Setya; Sumarni, Tri; Kurniawan, Wasis Eko (Jurnal Ilmiah Wahana Pendidikan, 2024)
The most health workers in hospitals are nurses who have important responsibilities in providing health services. In addition to the dominant number of nurses (50% - 60% of the entire workforce), nurses provide services 24 hours a day, for 7 days and have contact with patients. In addition, nurses are also human beings who do not escape the workload both in the institution where they work and in the family or in the community, which indirectly requires control and suitability in their lives. The quality of nurses' work life is the perception or assessment of nurses regarding all dimensions that affect the quality of their work life and are related to their experiences at work and in order to achieve goals. Quantitative descriptive research design with a cross sectional approach. The sample in this study were 67 respondents using simple random sampling technique. Data analysis with univariate analysis. The results showed that the majority of respondents aged 26-35 years with a good quality of work life as many as 30 respondents (44.8%), on the characteristics of gender the majority of respondents were female with a good quality of work life as many as 36 respondents (53.7%), on the characteristics of education the majority of respondents graduated from D3 with a good quality of work life as many as 29 respondents (43.3%), on the characteristics of the working period the majority of respondents with a working period ≥ 5 years with a good quality of work life as many as 33 respondents (49.3%).